Rolled-up single-layered vanadium oxide nanomembranes for microactuators with tunable active temperature. (11th June 2019) - Li, Xing; Wang, Yang; Xu, Borui; Zhou, Xuefei; Men, Chuanling; Tian, Ziao; Mei, Yongfeng
Abstract: Multilayer vanadium dioxide (VO2 ) actuators are a widespread concern as these micro/nano-actuators present a fast and efficient dynamic response when VO2 occurs in metal–insulator transition (MIT) at 68 °C. By tuning the O2 flow rate during oxide deposition and rolled-up nanotechnology, a microactuator based on a single-layered vanadium oxide nanomembrane with vertical component gradient is fabricated. Upward bending of the nanomembrane is driven by the release of the compressive strain gradient which is revealed through the difference in Raman shift of the vibration mode. Combining strain engineering, the initial curvature of microactuators is tuned in a wide range by the thickness of the nanomembranes. The actuation behavior from low curvature to high final curvature across the MIT is observed which depends on the nanomembrane thickness. Initial compressive strain distribution of the rolled-up nanomembrane decreases the MIT temperature simultaneously. Thus, taking advantage of the tunable MIT and reversible shape transformation, micro/nano-actuators with tunable triggering temperature, controllable initial curvature and large-displacement actuation are fabricated for curvature engineering in micromechanical systems.